2008
DOI: 10.1037/1045-3830.23.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of educational attainment in the Chicago Longitudinal Study.

Abstract: The authors investigated a comprehensive set of predictors of high school completion and years of completed education for youth in the Chicago Longitudinal Study, an ongoing investigation of over 1500 low-income, minority children who grew up on high-poverty neighborhoods. The study sample included 1286 youth for whom educational attainment could be determined by age 20. Predictors were measured from birth to high school from participant surveys and administrative records on educational and family experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 82 publications
8
150
0
4
Order By: Relevance
“…According to the theory of cultural and social reproduction, parental education is a major determinant of children's educational performance. Empirical research has confirmed the significant impact of parental education on a child's educational performance and attainment (e.g., Dubow et al 2009;Ou and Reynolds 2008). Against this background, we hypothesize that compared to other determinants of educational performance, such as occupational status and cultural possessions, parental education is a particularly strong predictor of children's educational performance (hypothesis 1).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
“…According to the theory of cultural and social reproduction, parental education is a major determinant of children's educational performance. Empirical research has confirmed the significant impact of parental education on a child's educational performance and attainment (e.g., Dubow et al 2009;Ou and Reynolds 2008). Against this background, we hypothesize that compared to other determinants of educational performance, such as occupational status and cultural possessions, parental education is a particularly strong predictor of children's educational performance (hypothesis 1).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
“…Schneider and Stevenson (1999) label it as an 'aligned ambition' a match between educational aspirations and occupational ambitions. The link between expectation and later attainment is agreed by Messersmith and Schulenberg (2008) and Ou and Reynolds (2008) state that adolescents' educational expectations predict their educational attainment. Students' motivation for post-secondary education can be as either an intrinsic or extrinsic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that influence school health and performance are also influenced by multiple social and dynamic factors in addition to intrinsic covariates, particularly parental education and socioeconomic status (SES) (Entwisle et al, 2005;Ou and Reynolds, 2008;Sirin, 2005). School facility quality, student health, and student performance likely reflect the overall socioeconomic status of a community based on funding provided by state and local governments (Condron and Roscigno, 2003).…”
Section: Confoundingmentioning
confidence: 99%